Transducer user syndrome: an occupational hazard of the ultrasonographer - Schoenfeld, Alex; Goverman, Jeremy; Weiss, Debra M; Meizner, Israel (European journal of ultrasound, 1999)
Since no study to date has assessed the prevalence of scanning-related disorders amongst sonographers in Obstetrics and Gynecology, we distributed a survey to all trained personnel in our ultrasound division. We evaluated the correlation between injuries sustained in the workplace, and factors such as age, gender, work load and intensity, scanning techniques, previous medical problems, and physical activity. Injuries included one or more of the following: carpal tunnel syndrome; carpal instability; tendinitis; back, shoulder, and neck pain; tingling and/or numbness in the extremities; weakness; and motion restriction. Of the 44 respondents, 29 (65%) have experienced some type of injury or symptom over the course of their scanning career. Five (12%) reported having missed work because of their symptoms, 15 (34%) have received orthopedic treatment (medication or physiotherapy), two (4.5%) have been diagnosed with carpal tunnel syndrome, and one (2.3%) with carpal instability based on electrophysiological examinations. These results demonstrate that ultrasound scanning in Obstetrics and Gynecology may pose an occupational risk for doctors and technicians.